Convalidation of an offense commited by a minor person beyond his/her civil capacity - Bus, Kateryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article examines the issue of convalidation of a deed committed by a minor outside of his civil legal capacity, which occupies an important place in the procedure of « healing» of invalid deeds.The relevance of this issue lies in the absence of a clearly defined legislative regulation of the procedure for the validation of a deed committed by a minor outside of his civil legal capacity, which in turn refers to the theoretical concepts of scientists, as well as the practice of national judicial bodies for the formation of a unified and legitimate approach to the understanding and enforcement of this question.The research analyzed the works of Ukrainian scientists, the current national legislation and judicial practice to clarify the legal nature of the deed validation committed by a minor outside of his civil capacity, which is the purpose of this research.Based on the results of the conducted research, the author came to the conclusion that the legislator allows and does not prohibit the validation of a deed committed by a minor outside of his civil legal capacity, with the aim of accepting and executing the deed by bona fide participants in the civil transaction, the occurrence of legitimate consequences for the participants of the deed and interested persons.This method of protection is used in the case of approval, absence of claims, and also, importantly, such a transaction is committed in the interests of a minor. In the opinion of the author, the legal issue of convalidation of a deed committed by a minor outside of his civil legal capacity should be specified in the updated Civil Code of Ukraine, by distinguishing between subjective and judicial invalidation, the grounds and conditions of its application as a way of protecting civil rights and interests.